In Syria [videorecording (DVD)] - Van Leeuw, Philippe; Abbass, Hiam; Bou Abboud, Diamand; Navis, Juliette (Film Movement series., 2018)
Trapped inside her house in a city under siege, a mother of three turns her flat into a safe fortress for her family and neighbours in an attempt to protect them from the war outside.